(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Periarthritis humeroscapularis is a very common condition that significantly affects working ability. The combination of multiple treatment methods, such as traditional medicine and physical therapy, to improve clinical effectiveness requires further evidence-based research. Objective: To evaluate the effectiveness of the herbal formula "Qiang huo sheng shi tang" combined with TENS (Transcutaneous Electrical Nerve Stimulation) in the treatment of Periarthritis humeroscapularis, and to monitor any adverse effects during the study. Methods: A controlled clinical intervention study with before-and-after comparisons was conducted on 60 patients diagnosed with Periarthritis humeroscapularis. The study group received the "Qiang huo sheng shi tang" combined with TENS (Transcutaneous Electrical Nerve Stimulation), while the control group received TENS alone. The treatment course lasted 14 days and was carried out at Tue Tinh Hospital from March 2025 to August 2025. Results: After 14 days of treatment, the study group receiving "Qiang huo sheng shi tang" combined with TENS showed significant improvement in pain level according to the 100mm VAS scale, shoulder joint range of motion according to the McGill–McRomi assessment, and pain and shoulder joint function according to the SPADI scale, compared with the control group that received TENS alone. No adverse effects were recorded during the study. Conclusion: The "Qiang huo sheng shi tang" combined with TENS is more effective in reducing pain and improving shoulder joint range of motion and function than TENS alone in the treatment of Periarthritis humeroscapularis, and it showed no adverse effects.